WHEN GLOBAL CIVILIZATION INITIATIVE MEETS PRACTICE – SHANGHAI COOPERATION ORGANIZATION - Trailović, Dragan; Popović, Slobodan (Serbian political thought, 2025)
Global Civilization Initiative (GCI) was launched in Beijing on March 15, 2023, when China’s President Xi Jinping delivered a speech titled Join Hands on the Path Towards Modernization at the CPC in Dialogue with World Political Parties High-level Meeting. For the purpose of this article, we will analyse the Shanghai Cooperation Organization (SCO), since we understand this organization as one of the best examples of implementing the Global Civilization Initiative in practice. This paper argues that the SCO, through its emphasis on multilateralism, non-interference, and a shared vision of regional security and development, embodies key concepts of the GCI’s proposed framework for international relations. By analysing the SCO’s foundational principles, its evolving institutional mechanisms, and its responses to regional challenges, this paper demonstrates how the organization fosters a "new type of international relations" characterized by dialogue, mutual respect, and a rejection of zero-sum approaches. The paper highlights the SCO’s role in promoting cultural exchange and civilizational diversity, thereby offering a practical example of how the GCI seeks to build a more inclusive and harmonious global order. We structured our research in this direction for several reasons. First, China launched both the Shanghai Cooperation Organization and the Global Civilization Initiative. Second, both are rooted in Chinese values, norms, and interpretations of international relations, security order, modernization, and the idea of building a shared future. Third, the SCO and GCI promote a framework in which civilizational differences are seen as drivers of mutual learning and solidarity, rather than as fault lines to justify the imposition of one’s own values, political systems, or economic models, or to fuel ideological confrontation. In this sense, both the SCO and GCI embrace cooperation as a guiding principle in shaping international relations. Both initiatives demonstrate that a strong sense of equality among actors contributes directly to a shared sense of togetherness. Last but not least, we consider it significant that both also serve China’s broader strategic interests—diplomatic, economic, security-related, developmental, and political.